Reduplication of Katingan Languange - Evie Evie (Dharma Duta, 2018)
The Indonesia consist of one thousand of island that spread out Sabang to Merauke, where the society live with the deferent of religion and culture. In Indonesia speak about local language. The near of ethnic groups have alone local language as the mean of communication between the members of society from ethnic group. The one of local language that exist in Central Kalimantan Province is Katingan Language. Katingan Language is one of the local language that used by population which live of all Katingan river. This language used as daily language in 6 subdisrict, they are: Katingan Hilir, Tasik Payawan, Tewang Sangalang Garing, Pulau Malan, Katingan Tengah, Katingan Hulu Katingan Region. Morpholoy is one branch of linguistics that study about the form of word include function and meaning of words. In this discussion is a part of morphology. In this discusstion especially will discuss about reduplication of Katingan language. Reduplication is the form of word that repeated for example: 1) Complete reduplication, 2) Affixed reduplication, 3) Partial reduplication, and Semantic reduolication.